THE REAL COST OF IRRIGATION-FED SENEGALESE RICE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Irrigated land accounts for barely five percent of African rice grown, yet absorbs about 50% of state aid for agriculture. Between 1975 and 1981 each tonne of irrigation-fed cereal in the Sahel received 60 times more subsidy than the equivalent...